2018
DOI: 10.1177/1055665618770307
|View full text |Cite
|
Sign up to set email alerts
|

22q11.2 Deletion Syndrome in Colombian Patients With Syndromic Cleft Lip and/or Palate

Abstract: The objective of this work was to identify 22q11.2 chromosomal deletion in patients with cleft lip and/or cleft palate and suggestive syndromic phenotype in Colombian patients. We studied 49 patients with cleft lip and/or cleft palate, exhibiting additional clinical findings linked to 22q11.2 deletion syndrome. All patients underwent high-resolution G-banded karyotyping, multiplex ligation-dependent probe amplification, and clinical evaluation by a geneticist. Seven patients presented 22q11.2 deletion and 2 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Although the studies did not report the specific location of microdeletions according to classical classification (proximal, central, and distal), we observed that the microdeletions in proximal locations (LCR-A until LCR-E) were the most frequent in pediatric patients with CHD and cleft lip and palate. Thus, the LCR affected by deletions in a Colombian population with 22q11.2DS were LCR-A-LCR-D (6/7, 85%) 72 ; in patients from Norway diagnosed with 22q11DS were LCR-A-LCR-D (53/57, 93%), LCR-A-LCR-B (3/57, 5%), LCR-A-LCR-C (1/57, 2%) 78 ; in a population from the Netherlands with 22q11.2DS were LCR-C-LCR-D (6/8, 75%), LCR-B-LCR-D (2/8, 15%) 79 ; in Chinese patients affected with microdeletion 22q11.2 were LCR-A-LCR-D (40/43, 93%), LCR-A-LCR-B (3/43, 7%) 80 ; in patients from the Netherlands with 22q11.2DS were LCR-C-LCR-D (15/27, 55.5%), LCR-B-LRC-D (12/27,44.5%), 42 and in a population from France with 22q11.2DS were LCR-A-LCR-D (8/15, 53.4%), LCR-A-LCR-B (2/ 15, 13.3%), LCR-A-LCR-C (2/15,13.3%), LCR-A-TBX1 (not mediated by LCRs) (2/15, 13.3%) LCR-B-LCR-D (1/15, 6.7%). 82 Some studies have focused on typing the deletion according to its size, which includes type I (3 Mb), type II (1.5), and type III (<1.5 Mb, atypical).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although the studies did not report the specific location of microdeletions according to classical classification (proximal, central, and distal), we observed that the microdeletions in proximal locations (LCR-A until LCR-E) were the most frequent in pediatric patients with CHD and cleft lip and palate. Thus, the LCR affected by deletions in a Colombian population with 22q11.2DS were LCR-A-LCR-D (6/7, 85%) 72 ; in patients from Norway diagnosed with 22q11DS were LCR-A-LCR-D (53/57, 93%), LCR-A-LCR-B (3/57, 5%), LCR-A-LCR-C (1/57, 2%) 78 ; in a population from the Netherlands with 22q11.2DS were LCR-C-LCR-D (6/8, 75%), LCR-B-LCR-D (2/8, 15%) 79 ; in Chinese patients affected with microdeletion 22q11.2 were LCR-A-LCR-D (40/43, 93%), LCR-A-LCR-B (3/43, 7%) 80 ; in patients from the Netherlands with 22q11.2DS were LCR-C-LCR-D (15/27, 55.5%), LCR-B-LRC-D (12/27,44.5%), 42 and in a population from France with 22q11.2DS were LCR-A-LCR-D (8/15, 53.4%), LCR-A-LCR-B (2/ 15, 13.3%), LCR-A-LCR-C (2/15,13.3%), LCR-A-TBX1 (not mediated by LCRs) (2/15, 13.3%) LCR-B-LCR-D (1/15, 6.7%). 82 Some studies have focused on typing the deletion according to its size, which includes type I (3 Mb), type II (1.5), and type III (<1.5 Mb, atypical).…”
Section: Discussionmentioning
confidence: 93%
“…The frequency of 22q11.2DS in the population of pediatric patients with CL/P varied between 0 and 14%. [67][68][69][70][71][72] In populations from Israel and South Asia, the prevalence of 22q11.2DS in CL/P patients was 0% (0/38 and 0/ 323, respectively). 67,71 In pediatric patients with CL/P from Germany, the prevalence of syndrome was 2% (3/101).…”
Section: Presence Of Cl/p In Pediatric Patients With the 22q112 Microdeletionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 22q11.2 deletion syndrome (also known as DiGeorge or Velocardiofacial syndrome) is the most common deletion syndrome in humans, 20 occurring in 1 to 4 per 6000 live births 21 and is caused by hemizygous micro-deletions on chromosome 22q11.2 22 ; this syndrome has been associated with many different malformations with different severity, commonly includes conotruncal cardiac defects, palatal abnormalities, renal anomalies, immune deficiency (defects in T cells and short telomeres), facial anomalies, developmental delay, learning, and behavioral problems. 23 - 25 The typical combination of hypocalcemia, immunodeficiency, and cardiac defects may lead the clinician to suspect this diagnosis; however, there are cases in which the patient presents with an isolated defect, in which the most reported is the congenital heart disease. 7 , 26 The variation in the clinical findings delays the diagnosis, as evidenced in the study by Cancrini et al 27 in 228 patients with 22q11.2 deletion syndrome.…”
Section: Discussionmentioning
confidence: 99%